Comparative sequence analysis of primate subtelomeres originating from a chromosome fission event - Rudd, M. Katharine; Endicott, RaeLynn M.; Friedman, Cynthia; Walker, Megan; Young, Janet M.; Osoegawa, Kazutoyo; NISC Comparative Sequencing Program; de Jong, Pieter J.; Green, Eric D.; Trask, Barbara J. (Genome Research, 2009)
Subtelomeres are concentrations of interchromosomal segmental duplications capped by telomeric repeats at the ends of chromosomes. The nature of the segments shared by different sets of human subtelomeres reflects their high rate of recent interchromosomal exchange. Here, we characterize the rearrangements incurred by the 15q subtelomere after it arose from a chromosome fission event in the common ancestor of great apes. We used FISH, sequencing of genomic clones, and PCR to map the breakpoint of this fission and track the fate of flanking sequence in human, chimpanzee, gorilla, orangutan, and macaque genomes. The ancestral locus, a cluster of olfactory receptor (OR) genes, lies internally on macaque chromosome 7. Sequence originating from this fission site is split between the terminus of 15q and the pericentromere of 14q in the great apes. Numerous structural rearrangements, including interstitial deletions and transfers of material to or from other subtelomeres, occurred subsequent to the fission, such that each species has a unique 15q structure and unique collection of ORs derived from the fission locus. The most striking rearrangement involved transfer of at least 200 kb from the fission-site region to the end of chromosome 4q, where much still resides in chimpanzee and gorilla, but not in human. This gross structural difference places the subtelomeric defect underlying facioscapulohumeral muscular dystrophy (FSHD) much closer to the telomere in human 4q than in the hybrid 4q–15q subtelomere of chimpanzee.
10.1101/gr.083170.108